Improving timely submission of weekly sales call report to help increase sales performance in field sales division - De Castro, Peter John B. (Animo Repository, 2017)
The purpose of this action research is to improve the timely submission of Weekly Sales Call Report of Field Sales Officers in the Bank of the Philippine Islands (BPI) and in the process, improve the Sales Performance of Field Sales Division. I collaborate with the Field Sales management team, Field Sales Support, and my fellow Cluster Managers and Field Sales Officers to craft the best solution that addresses the late submission of the weekly sales call report. The solutions include two cycles. The first one is through constant reminders while the second one involves transforming the weekly report template. The cooperation within the team translates to an average of 88% on-time submission of the Weekly Journal in our division. The success of this research provides motivation for future studies involving reports and actual sales performance.